Study of Mn²⁺ and MnO₄⁻ products interaction in alkaline solution - Sofronov, D.S.; Odnovolova, A.M.; Gudzenko, L.V.; Desenko, S.M.; Mateychenko, P.V.; Rudenko, L.V.; Lebedynskiy, A.M. (Functional Materials, 2017)
Interaction of Mn²⁺ ions with MnO₄⁻ in alkaline medium is considered. The main component of this interaction is manganese oxyhydroxide MnO(OH) and not manganese dioxide, that is revealed by means of X-ray diffraction analysis, IR-spectrometry and chemical analysis. It is demonstrated that decomposition of MnO(OH) occurs in the wide temperature range (60-550 °C), that results in mixture of Mn₂O₃ and MnO₂ oxides formation.